NMR-based metabolomics reveals the metabolite profiles of Vibrio parahaemolyticus under blood agar stimulation - Zhou, Jun; Zhang, Chundan; Han, Jiaojiao; Lu, Chenyang; Li, Ye; Ming, Tinghong; Su, Xiurong (Archives of microbiology, 2020)
Vibrio parahemolyticus is a halophilic bacterium which causes widespread seafood poisoning pathogenicity. Although the incidence of disease caused by V. parahemolyticus was stepwise increased, the pathogenic mechanism remained unclear. Herein, the difference of V. parahemolyticus ’s metabonomic which on blood agar and seawater beef extract peptone medium was detected via nuclear magnetic resonance and 55 metabolites were identified. Among them, 40 kinds of metabolites were upregulated in blood agar group, and 12 kinds were downregulated. Nine pathways were verified by enrichment analysis which were predicted involved in amino acids and protein synthesis, energy metabolism, DNA and RNA synthesis and DNA damage repair. We supposed that the metabolic pathway obtained from this study is related to V. parahemolyticus pathogenicity and our findings will aid in the identification of alternative targets or strategies to treat V. parahemolyticus -caused disease.